Electroactive gellan gum/polyaniline spongy-like hydrogels - Srisuk, Pathomthat (2018)
he ability of electroactive materials to influence and modulate cell behavior has been revealing great potential, especially in the field of skeletal muscle tissue engineering. Herein, we propose PANi-GG electroactive spongy-like hydrogels as potential materials to modulate myoblast bioresponse. polyaniline (PANi) adds electroconductiviy to gellan gum (GG) spongy-like hydrogels that hold a high resemblance to the extracellular matrix (ECM), that is, water content, mechanical properties, and microarchitecture, and that can be further tuned to meet muscle tissue properties. For this purpose, PANi-GG spongy-like hydrogels were obtained by ionically cross-linking with calcium chloride (CaCl2) and further in situ aniline polymerization through oxidation with ammonium persulfate (APS) in a molar ratio of 1:1.05. The physicochemical characterization, surface morphology, electro-conductivity, and mechanical performance were assessed by FTIR, SEM, four-point probe technique, and compression testing, respectively. The viability and proliferation of L929 was not compromised after direct contact of PANi-GG spongy-like hydrogels with L929 cells, as determined by MTS assay and DNA quantification, respectively. C2C12 myoblasts were entrapped within the electroactive materials and cells adhered and spread. Moreover, cells proliferated along the cell culture period showing myosin expression after 7 days of culture. These results highlight that PANi-GG spongy like hydrogels are attractive candidates to be used in skeleton muscle tissue engineering.